The Effect and Optimal Dosage of Dexmedetomidine Plus Sufentanil for Postoperative Analgesia in Elderly Patients With Postoperative Delirium and Early Postoperative Cognitive Dysfunction: A Single-Center, Prospective, Randomized, Double-Blind, Controlled Trial - Zhao, Wenshuai; Hu, Yanan; Chen, Hui; Wang, Xifan; Wang, Liping; Wang, Yu; Wu, Xiaohong; Han, Fei (Frontiers in Neuroscience, 2020)
Background: Postoperative delirium (POD) and postoperative cognitive dysfunction (POCD) are common complications among elderly patients after major surgery. Dexmedetomidine (DEX) is less frequently explored for its effects on postoperative neurocognitive disorders. This study investigated the effect and optimal dosage of DEX for patient-controlled analgesia (PCA) on POD and early POCD among elderly patients after major surgery. Methods: Patients in four groups received continuous infusion of DEX 0, 100, 200, and 400 μg with sufentanil 150 μg for PCA immediately after surgery. The POD and POCD were assessed on postoperative days 1, 2, 3, and 7 based on the Confusion Assessment Method scale and the Mini-Mental State Examination scale. The sedation level, postoperative pain intensity, and side effects were assessed. The trail was registered at the Chinese Clinical Trial Registry (ChiCTR-IPD-17010950, Principal investigator, Fei Han, Date of registration, March 22, 2017). Results: The overall incidence of POD and early POCD in the DEX 200 μg group and the DEX 400 μg group was lower than that in the DEX 0 μg group and the DEX 100 μg group 7 days after surgery (P < 0.05). Compared with DEX 200 μg, DEX 400 μg reduced early POCD in patients undergoing open surgery (P < 0.05). There was no difference in postoperative sedation level, postoperative pain intensity, or side effects in all groups. Conclusions: The continuous infusion of DEX 200 μg or DEX 400 μg in PCA significantly decreased the incidence of POD and early POCD after major surgery without increasing any side effects. Compared with DEX 200 μg, DEX 400 μg was preferred for reducing early POCD in patients undergoing open surgery.